PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK (LKPD) BERBASIS MODEL INKUIRI TERBIMBING UNTUK MENINGKATKAN KETERAMPILAN PROSES SAINS PADA MATERI DUNIA HEWAN (ANIMALIA) KELAS X SMA - Lestari, Sharaswati Budi; Febrita, Elya; Syafii’i, Wan (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The purpose of this research is to produce a valid students worksheet based on guided inquiry to increasing science process skill on kingdom (animalia) material. This research was conducted at the Laboratory of Biology Education Department of PMIPA FKIP University of Riau andSenior High School2 Bangko Pusako Kab.Rokan Hilir in Mei-September 2017. This type of research is a development research using ADDIE model conducted up to development stage. There are 6 students worksheet developed. The instruments of data collection in this research are students worksheet assessment / validation sheets, and student response questionnaires. After students worksheet was developed, validated by 4 validators are 2 lecturer UR and 2 teacher Biology in Kab.Rokan Hilir and then simulation on 12 students Biology in 2015 Education FKIP UR, and trial limited on 20 students of Class X in Senior High School 2 Bangko Pusako Kab. Rokan Hilir. The validation result shows that the score of feasibility aspect of design of 6 LKPD developed is 3.39 valid categories, the mean score of pedagogical aspect is 3.35 very valid categories, and the the answer aspect score is 3.52 very valid categories. The average score of all aspects of the six LKPD is 3.42 very valid categories. The results of the simulation test showed a mean score of 3.37 with very good category. The results of the trial limited showed the average score of 3.37 with very good category. The results of the answer analysis on trial limited showed the average value of 81 (non experimen) with good category. The results of the second answer analysis on trial limited showed the average value of 83 (experimen) with good category. The.validition LKPD to increase science process skill on the kingdom (animalia) material for tenth grade senior high school category valid and very good.Keywords: Development, LKPD, Guided Inquiry, Science process skill, Kingdom (Animalia)